Tuned mass damper system of high-rise intake towers optimized by improved harmony search algorithm. (1st May 2017) - Zhang, H.Y.; Zhang, L.J.
Highlights: TMD is proposed to overcome the whiplash effect of the high-rise intake tower. The developed simplified model can well describe the dynamic characteristics and seismic response of the intake tower. IHS is employed to optimize the mass, frequency and damping ratio of the TMD. The TMD optimized by IHS has good robustness and superiority. The TMD can improve the seismic resistance of the intake tower in the dynamic displacement, acceleration and stress. Abstract: The seismic safety and proper functioning of intake towers in a major earthquake are very crucial to the whole hydraulic project, since the controlled release of the reservoir could help to prevent catastrophic failure of a dam after an earthquake by reducing the water pressure. In this study, the tuned mass damper (TMD) system was introduced into the seismic design of high-rise intake towers. The installation of TMD can effectively dissipate the seismic energy acting on the intake tower and thus overcome the whiplash effect of the hoist room. The 3D finite element model of the intake tower was simplified into a 2D MDOF model. Improved harmony search (IHS) algorithm was used to determine the optimal parameters for the TMD systems using Matlab, and the robustness of the TMD systems was investigated. The simulation elements of the TMD system were incorporated into ADINA to simulate and evaluate the effect of the TMD system on the dynamic displacement and stress responses of various key points of the intake tower to different seismic excitations.